Wsp1 Is Downstream of Cin1 and Regulates Vesicle Transport and Actin Cytoskeleton as an Effector of Cdc42 and Rac1 in Cryptococcus neoformans - Shen, Gui (American Society for Microbiology, 2012)
Human Wiskott-Aldrich syndrome protein (WASP) is a scaffold linking upstream signals to the actin cytoskeleton. In response to intersectin ITSN1 and Rho GTPase Cdc42, WASP activates the Arp2/3 complex to promote actin polymerization. The human pathogen Cryptococcus neoformans contains the ITSN1 homolog Cin1 and the WASP homolog Wsp1, which share more homology with human proteins than those of other fungi. Here we demonstrate that Cin1, Cdc42/Rac1, and Wsp1 function in an effector pathway similar to that of mammalian models. In the cin1 mutant, expression of the autoactivated Wsp1-B-GBD allele partially suppressed the mutant defect in endocytosis, and expression of the constitutively active CDC42(Q61L) allele restored normal actin cytoskeleton structures. Similar phenotypic suppression can be obtained by the expression of a Cdc42-green fluorescent protein (GFP)-Wsp1 fusion protein. In addition, Rac1, which was found to exhibit a role in early endocytosis, activates Wsp1 to regulate vacuole fusion. Rac1 interacted with Wsp1 and depended on Wsp1 for its vacuolar membrane localization. Expression of the Wsp1-B-GBD allele restored vacuolar membrane fusion in the rac1 mutant. Collectively, our studies suggest novel ways in which this pathogenic fungus has adapted conserved signaling pathways to control vesicle transport and actin organization, likely benefiting survival within infected hosts.